PENGARUH PEMBERIAN JUS BUAH NAGA TERHADAP PERUBAHAN KADAR PROFIL DARAH IBU HAMIL DENGAN ANEMIA YANG MENDAPATKAN SUPLEMENTASI TABLET FE - Stefani Anastasia Sitepu; Vitrilina Hutabarat (Jurnal Online Keperawatan Indonesia, 2020)
Anemia is a reduced number of red blood cells or hemoglobin content in the blood. The largest group that can experience anemia are pregnant women. Causes of anemia in pregnant women include the production of hemoglobin chains due to certain diseases or experiencing impaired hemoglobin production due to a lack of iron, folic acid or vitamin B12. Existing research states that dragon fruit can overcome anemia, where dragon fruit contains substances that the body needs for the formation and maturation of blood cells. The research objective was to determine the effect of dragon fruit juice on changes in blood profile levels in pregnant women with anemia who received iron supplementation. The research method used was a quasi-experimental design with a nonrandomized pretest and posttest design with control group design. This research was conducted for 7 weeks. The number of samples in this study were 40 respondents (20 respondents in the intervention group who received dragon fruit juice and Fe tablet supplementation and 20 respondents who only received iron tablet supplementation). Samples were obtained using purposive sampling. Evaluation of blood profile levels was carried out after giving dragon fruit juice on day 15. The results showed an increase in hemoglobin, hematocrit, and erythrocyte levels (p = 0,000), meaning that giving dragon fruit juice to pregnant women with anemia had an effect on increasing hemoglobin levels. hematocrit, and erythrocytes. For health services, it is hoped that dragon fruit juice can be used as an alternative in overcoming anemia in pregnant for women.